2015
DOI: 10.1177/0022034515601658
|View full text |Cite
|
Sign up to set email alerts
|

Pulp-dentin Regeneration

Abstract: The goal of regenerative endodontics is to reinstate normal pulp function in necrotic and infected teeth that would result in reestablishment of protective functions, including innate pulp immunity, pulp repair through mineralization, and pulp sensibility. In the unique microenvironment of the dental pulp, the triad of tissue engineering would require infection control, biomaterials, and stem cells. Although revascularization is successful in resolving apical periodontitis, multiple studies suggest that it alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(41 citation statements)
references
References 61 publications
0
37
0
Order By: Relevance
“…Moreover, the proliferation potential of DPSCs is comparable to other types of MSC-like cells [1]. Despite the availability and the stemness of DPSCs, the potential applications and preclinical efficacy of DPSCs have been limited to the regeneration of pulp and dentin [42]. In this study, we further investigated the applicability of DPSCs in in vivo angiogenesis, which is one of the main huddles to overcome for successful tissue-engineered constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the proliferation potential of DPSCs is comparable to other types of MSC-like cells [1]. Despite the availability and the stemness of DPSCs, the potential applications and preclinical efficacy of DPSCs have been limited to the regeneration of pulp and dentin [42]. In this study, we further investigated the applicability of DPSCs in in vivo angiogenesis, which is one of the main huddles to overcome for successful tissue-engineered constructs.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, several pre-clinical human models demonstrated the potential utility of tissue engineering-based strategies in regenerating pulp–dentin complex, particularly for necrotic or immature permanent teeth 144 . A recent study using pulpal MSCs showed promising results in pulp–dentin regeneration in vivo through autologous transplantation, 145 reinforcing the notion that DPSCs may be used for successful dental tissue engineering 146 …”
Section: Dental and Periodontal Tissue Engineeringmentioning
confidence: 97%
“…A novel treatment of pulp revascularization/regeneration is an effective approach for inducing root maturation (Iwaya et al, 2001;Banchs and Trope, 2004). During revascularization/regeneration procedures, the evoked-bleeding step leads to a substantial influx of stem cells from dental apical papilla (SCAPs) into the root canal, which contributes to root development and apical closure (Cao et al, 2015). However, several histological findings reported that most tissues formed in the canal of the revitalized immature permanent tooth lack organized pulp-dentin complex and consist of ectopic bone, fibrous tissues, and cementum (Martin et al, 2012;Saoud et al, 2015;Peng et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the root canal space became partly obliterated with ectopic bone (Martin et al, 2012;Saoud et al, 2015). It is presumed that stem cells from alveolar bone would migrate into the root canal and initiate ectopic calcification deposition (Cao et al, 2015;Saoud et al, 2015). Mesenchymal stem cells (MSCs) from different dentoalveolar tissues are unique and retain identities from their direct tissue sources.…”
Section: Introductionmentioning
confidence: 99%